Applications of Physics in Diagnostic Imaging - Kholmatov Jasurbek Abdikhoshimovich; Askarov Osim Olimdjanovich; Hansie Pilania; Kunal Vijay Kawale (Journal of Medical Genetics and Clinical Biology, 2024)
This article will explore the various ways in which physics is applied in diagnostic imaging, with a focus on X-ray, computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound. Diagnostic imaging has become a cornerstone of modern medicine, since the advent of radiography. Over the years, various diagnostic imaging techniques have been developed, each with its indications and contraindications. However, all diagnostic imaging techniques have one underlying commonality: they rely on the fundamental principles of physics. Consequentially, it becomes of further importance to know and understand the concepts of applied physics, to produce better healthcare professionals.